Effect of Lipid-Lowering Treatment on Factor VII Profile in Hyperlipidemic Patients - Porreca, Ettore; Di Febbo, Concetta; Amore, Concetta; Di Castelnuovo, Augusto; Baccante, Giovanna; Donati, Maria Benedetta; Cuccurullo, Franco; Iacoviello, Licia (Thrombosis and Haemostasis, 2000)
A link has been suggested between blood lipids and hemostatic activation. Factor VII (FVII) is a coagulation factor which plays a pivotal role in fibrin generation and thrombus formation. Clinical trials have demonstrated that inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase greatly reduce cardiovascular events in patients with and without coronary artery disease but few data, at this time, are available on the effects of lipid-lowering treatment on factor VII levels. We studied thirty-six IIA and IIB type hyperlipidemic patients who, after a preliminary period of lipid-lowering diet, added atorvastatin (20 mg/daily) or continued dietary treatment alone until they achieved LDL-C recommended levels (< 4 mmol/L). Four to six weeks of lipid lowering treatment with diet plus atorvastatin, produced a significant reduction in FVII coagulant activity (FVIIc) and antigen (FVIIAg). No significant changes were observed in activated FVII (FVIIa). The lipid-lowering treatment with diet alone induced an improved lipid pattern, but no significant changes in FVII profile. Our study suggests a significant effect of lipid-lowering treatment on FVII levels. A possibile nonlipid mechanism that modifies FVII pathway may be suggested.
Keywords: Factor VII; hyperlipdemia; statins